Fidyah between Classical Fiqh and Institutional Governance: Social Welfare and Sustainable Justice in Contemporary Indonesia - Syam, Aydi; Abd Wahhab Abd Qawiy, Salih Ahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
Background: The determination of fidyah for individuals unable to fast during Ramadan has traditionally been grounded in classical Islamic jurisprudence, which prescribes the provision of staple food to the poor as compensation. In contemporary Muslim societies, however, this obligation is increasingly mediated through institutional governance and monetary valuation Aims: This article examines the transformation of fidyah between classical fiqh and institutional governance, focusing on how BAZNAS reframes fidyah from a food based juristic obligation into a monetary instrument of Islamic social welfare. This study analyzes it as a site of authority negotiation between juristic doctrine, state recognized religious institutions, local economic realities, and the lived legal practices of Muslim communities Method: Methodologically, the study employs legal hermeneutics and thematic analysis of Qur’anic foundations, hadith reports, classical juristic interpretations, BAZNAS policy documents, and contemporary scholarship on Islamic social finance, maqasid al sharia, and legal pluralism Findings: The findings reveal that while classical jurisprudence generally defines fidyah as one mud of staple food per day, the institutional determination of IDR 65,000 reflects a contextual adaptation based on contemporary food consumption patterns and economic conditions. This transformation produces a socio legal tension: monetary standardization may enhance the welfare of recipients and support food security, but it may also challenge local fiqh practices and burden economically vulnerable payers if regional economic differences are ignored. Implication: The article argues that fidyah should be understood through a maqasid based framework in which hifz al nafs, hifz al mal, and human dignity guide the ethical governance of Islamic social finance. It also underscores the role of institutional interpretation in promoting sustainable justice by ensuring that fidyah remains responsive to the needs of vulnerable communities. Originality: Its originality lies in repositioning fidyah from a marginal ritual topic into a lived legal mechanism of sustainable justice, where classical fiqh, institutional authority, and grassroots economic realities continuously negotiate one another in contemporary Indonesia